2021
DOI: 10.20525/ijrbs.v10i1.1020
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and psychological empowerment on service performance mediated by organizational citizenship behavior Islamic perspective (OCBIP)

Abstract: This study aims to determine and analyze the influence of perceived organizational support, psychological empowerment, and organizational citizenship behavior from an Islamic perspective to service performance, as well as the mediation role of organizational citizenship behavior from an Islamic perspective on the relationship between perceived organizational support and psychological empowerment on service performance. The population of this study is all employees of food processing industry companies in Yogya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a similar vein, Marfuatun and Muafi (2021) examined the positive correlation between POS and innovation, encompassing both individual and group levels. Their research was conducted among a cohort of 112 employees hailing from the Indonesian food processing sector.…”
Section: Perceived Organizational Support Empowerment and Innovationmentioning
confidence: 99%
“…In a similar vein, Marfuatun and Muafi (2021) examined the positive correlation between POS and innovation, encompassing both individual and group levels. Their research was conducted among a cohort of 112 employees hailing from the Indonesian food processing sector.…”
Section: Perceived Organizational Support Empowerment and Innovationmentioning
confidence: 99%
“…Below is the division of these keyword clusters. (Samier & Elkaleh, 2021) (Soemitra et al, 2022) (Marfuatun & Muafi, 2021) (Nurasyiah et al, 2021) (Hadi et al, 2021) (Amelia et al, 2019) (Purnomo et al, 2015) (Ramadhanu & Widiastuti, 2017) (Zein et al, 2020) (Ridwan et al, 2019) (Hashim et al, (Fathoni & Rohim, 2019) (Farooq & Ssekamanya, 2018) (Nadzir, 2015)…”
Section: Figure 3 Three Fields Plotmentioning
confidence: 99%
“…OCB refers to -Unrecognized individual behavior both implicitly and explicitly through a formal reward system that supports the effectiveness and efficiency of an organization as a whole‖ (Marfuatun & Muafi, 2021, p.17). Based on the previous description, OCB was treated as extra-role performance (Marfuatun & Muafi, 2021). The results of Hsiao et al (2015) showed that organizational citizenship behavior (OCB) of hotel employees was positively affected by the level of perceived gender diversity.…”
Section: Women Empowerment and Employee Outcomes (Performance And Ocb)mentioning
confidence: 99%